Long-term return to sports after anterior cruciate ligament injury: Reconstruction vs no reconstruction—A comparison of 2 case series - Keays, S. L.; Mellifont, D. B.; Keays, A. C.; Stuelcken, M. C.; Lovell, D. I.; Sayers, M. G. L. (The American Journal of Sports Medicine, 2022)
Background: Reconstruction is considered to provide the best opportunity for return to sports (RTS) after anterior cruciate ligament (ACL) rupture. However, recent studies report that <50% of athletes return to preinjury sporting levels and that RTS rates at 1 year after injury are the same for athletes undergoing reconstruction and nonoperative management. Long-term studies are essential to confirm these findings and guide decisions regarding surgery.